2002
DOI: 10.1007/s102660200004
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes in the granular convoluted tubule cells of the mouse submandibular gland following hypophysectomy and hormonal replacement

Abstract: Morphological changes in the granular convoluted tubule (GCT) cells of the male mouse submandibular gland (SMG) were examined following hypophysectomy and hormonal replacement. Semithin sections stained with Heidenhain's iron hematoxylin showed that hypophysectomy severely regressed the GCT phenotype. Although only a few dispersed cells containing secretory granules were observed in the GCT segments under a light microscope, electron microscopy revealed that many regressed cells continued to constitutively ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 21 publications
4
16
2
Order By: Relevance
“…We confirmed that essentially all of the immature GCT cells in the glands of prepubertal mice stained positive for mK1, whereas after the onset of puberty, many of the cells differentiated into full-fledged granular cells and became negative for mK1 . We also confirmed that all the atrophied GCT cells following hypophysectomy were mK1-positive, whereas, many of the GCT cells that developed a granular cell phenotype after hormone replacement therapy (Kurabuchi 2002) became mK1-negative . Taken together, these findings suggest that mK1 is a marker of granular duct cells with a poor granular cell phenotype.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…We confirmed that essentially all of the immature GCT cells in the glands of prepubertal mice stained positive for mK1, whereas after the onset of puberty, many of the cells differentiated into full-fledged granular cells and became negative for mK1 . We also confirmed that all the atrophied GCT cells following hypophysectomy were mK1-positive, whereas, many of the GCT cells that developed a granular cell phenotype after hormone replacement therapy (Kurabuchi 2002) became mK1-negative . Taken together, these findings suggest that mK1 is a marker of granular duct cells with a poor granular cell phenotype.…”
Section: Introductionsupporting
confidence: 74%
“…The animals were housed under controlled environmental conditions (22掳C, LD 12 h:12 h), and provided with food and water ad libitum. At 12 weeks of age, the hypophysectomized mice were divided into eight groups, each group consisting of at least five animals, and injected with hormones as described in our previous papers (Kurabuchi 2002(Kurabuchi , 2006Kurabuchi et al 2002. In brief, the doses (per kg body weight) per injection of the hormones were as follows: 5a-dihydrotestosterone (DHT: Wako Ltd., Osaka, Japan), 20 mg; dexamethasone (Dex: Wako Ltd., Osaka, Japan), 10 mg; 3,5,3 0 -triiodo-L thyronine (T 3 : ICN Biochem, Aurora, Ohio, USA), 1 mg.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…8,16 Briefly, small pieces of the fixed SMGs, as described above, were dehydrated in a graded series of ethanol solutions and embedded in epoxy resin. Deresined 1-碌m-thick sections were stained with Heidenhain's iron hematoxylin for the lightmicroscopy examination.…”
Section: Light-and Electron-microscopy Proceduresmentioning
confidence: 99%
“…Our group's previous studies using adult male mice suggest that T 3 alone induces a normal female-like GCT phenotype in the glands of Hypox males. 8,14,15 However, because the disappearance of the GID cells after puberty was irreversible, the effects of thyroid hormones on GID cells in adult male glands could not be elucidated. To define the role of thyroid hormones in the morphological aspects of GID cells, the present experimental series examined the effects of thyroid hormones on the SMGs of female mice.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation